Post-Caldera Eruptions at Chalupas Caldera, Ecuador: Determining the Timing of Lava Dome Collapse, Hummock Emplacement and Dome Rejuvenation - Córdova, Marco D.; Mothes, Patricia Ann; Gaunt, H. Elizabeth; Salgado, Josué (Frontiers in Earth Science, 2020)
Chalupas is a late-Pleistocene silicic collapse caldera that lies astride the Eastern Cordillera in central Ecuador and is the second largest caldera collapse feature in the Northern Volcanic Zone. Its VEI 7 eruption, which occurred ~0.21 Ma, has garnered the attention of the volcanological community. Earlier studies focused on developing a magmatic model of the volcano, including its geothermal potential. Our research highlights new observations of the post-caldera activity at Chalupas, beginning with the resurgent stratovolcano Quilindaña (~0.170 Ma), followed by the formation of the Buenavista dome, at a similar age of about 0.180 Ma, 5 km eastward of Quilindaña´s summit. At the eastern foot of Buenavista dome we identify hummocky terrain covering an area of 20 km2. Geological observations and sampling, laboratory analysis (geochemistry, Scanning Electron Microscope (SEM) analysis and radiometric dating) combined with modern field and remote sensing techniques are employed to highlight geological features that may be indicative of the provenance of the hummocks and to demonstrate that the hummocky topography may have originated from gravitational breccia flows from the dome´s eastern flank. Numerical simulations were undertaken to represent breccia flow transit and emplacement over the present landscape and to view the potential hazard footprints from Buenavista dome. We employed volumes of 20 to 120 Mm3 to see footprints of mass flow deposition and how the traces correspond to the present hummock landscape. This study has provided the opportunity to establish a closer integration between modeling with two gravity flow transit programs (LaharZ/PFz and VolcFlow) while also employing a high-resolution digital elevation model (DEM), field sampling, correlation with SEM images and geochronology to provide a picture of the hazard footprints that a volcanic mass flow of +100 Mm3 volume might generate if sourced from the present Buenavista dome. Rejuvenation of Buenavista dome is represented by several small eruptions, whose tephras are dated at about 40 ky BP, and which occurred after Buenavista´s partial collapse. Our new data contribute to the overall knowledge about Chalupas and demonstrates that the caldera has produced more recent eruptive activity than was previously recognized.